Unveiling the Potential of Perineural Injection Therapy in Trigeminal Neuralgia Management - Vivid Prety Anggraini; Razi, Fakhrur (Surabaya Physical Medicine and Rehabilitation Journal, 2025)
Trigeminal neuralgia is characterized by severe pain that is restricted to the trigeminal nerve and frequently causes abrupt, severe bouts in the face. About 80% of cases of classical trigeminal neuralgia are classed as idiopathic. With the use of the Numeric Rating Scale (NRS) and the SF-36 questionnaire, this case study aims to determine how perineural injection therapy (PIT) affects pain relief in early trigeminal neuralgia cases and how it can affect patient function. The patient presented with a history of 8 years persistent facial pain, localized to the right side of the face. Described as sharp and intermittent, the pain rated between 6 on the Numeric Rating Scale (NRS). It was exacerbated by activities such as chewing and combing, yet alleviated by rest and medication. Injections of a 5% dextrose solution in sterile water (D5W) are administered subcutaneously and intracutaneously at the trigeminal nerve point. The PIT has been performed three times. with an injection interval of 2-3 weeks. Injections are made at the trigeminal nerve point, based on the Lyftogt book. The NRS score on first injection was changed from 6 to 2, second injection was from 2 to 1, and third injection was 1 before and after injection. The quality of life is better than before. SF-36 questionnaire showed a change from 50-75% on first injection, 75-100% on second injection, and 100% on the third injection. This study showed that PIT can improve patient's pain and patient's quality of life.